Bronchial sleeve resection with complete pulmonary preservation - Tomaszewski, Dariusz; Dziedzic, Robert; Rzyman, Witold (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction : Bronchial sleeve resection (BSR) with total pulmonary preservation is a treatment option in cases limited to the main bronchus. Our 20 years of experience in application of BSR are presented, especially considering indications, operative techniques, and treatment results of this group of patients. Material and methods : From 1991 to 2010, 20 patients underwent surgical treatment using the BSR method. This procedure was indicated for traumatic bronchial separation in 4 cases, tumour of the main bronchus in 10 cases, benign constriction of the anastomotic stenosis after sleeve resection in 2 cases, and pathology of the bronchial stump after lobectomy in 4 cases. All patients underwent posterolateral thoracotomy. In 9 ca- ses BSR of the left main bronchus was performed, in 6 cases of the right main bronchus, in 2 cases of the carina, and in 3 cases of the distal part of the main bronchus. All procedures were performed using continuous, monofilament, late absorbable suture, with no tissue covering except one case. Routinely, anastomotic tension was decreased with release of the hi- lum. In cases of carinal resection, additionally the anterior wall of the trachea was exposed and the chin was sewed to the an- terior surface of the chest. Results : There were no postoperative deaths. Mean length of stay was 9 days (from 4 to 15). Two patients (10.5%) had a prolonged air leak. One patient died as a result of circulatory insufficiency 45 months after BSR. Two patients were lost to follow-up after 54 and 60 months following uneventful surgical treatment. Seventeen patients are still alive, one with recurrence of neoplastic disease. Conclusions : For the selected group of patients BSR seems to be an effective and safe method of surgical treatment resulting in good long-term survival rates.